Evaluation of Six Novel Protein Sources on Apparent Digestibility in Pacific White Shrimp, Litopenaeus vannamei - Xiaoyue Li; Yongkang Chen; Chaozhong Zheng; Shuyan Chi; Shuang Zhang; Beiping Tan; Shiwei Xie (Aquaculture Nutrition)
This study is aimed at evaluating the apparent digestibility coefficients (ADC) of six novel protein sources in Pacific white shrimp (Litopenaeus vannamei), including black soldier fly larvae meal (BSFLM), Chlorella vulgaris meal (CM), cottonseed protein concentrate (CPC), Tenebrio molitor meal (TM), Clostridium autoethanogenum protein (CAP), and methanotroph (Methylococcus capsulatus, Bath) bacteria meal (BPM). The control diet (CD) was formulated to contain 448.8 g/kg crude protein and 71.8 g/kg crude lipid. Then, six experimental diets were formulated to contain 70% CD and 30% test ingredients. The yttrium oxide was used as an exogenous indicator for apparent digestibility detection. Six hundred and thirty healthy and uniform-sized shrimp (approximately 3.04±0.01 g) were randomly distributed into triplicate groups of 30 shrimp and they were fed three times daily. After the shrimp was acclimating for one week, their feces were collected 2 hours after the morning feeding until sufficient samples were available for compositional analysis to calculate apparent digestibility. The apparent digestibility coefficients for a dry matter of diets (ADCD) and ingredients (ADCI) as well as the apparent digestibility coefficients for crude protein (ADCPro), crude lipid (ADCL), and phosphorus (ADCP) of test ingredients were calculated. Results showed that the growth performance of shrimp fed BSFLM, TM, and BPM diets significantly decreased compared to that fed the CD (P<0.05), and no significant differences were found among those fed CD, CM, CAP, and CPC diets (P>0.05). There were no significant differences in survival among each group (P>0.05). As for the diets, results showed that the ADCD of BSFLM, CM, CPC, and TM diets was significantly lower than that of CD, while that of the CAP diet was significantly higher than that of CD (P<0.05) and there were no significant differences between BPM and CD diets (P>0.05). As for the test ingredients, the ADCPro and ADCL of BSFLM, CM, CPC, and TM were significantly lower than those of CD in Litopenaeus vannamei (P<0.05). The ADCPro of CAP was significantly higher than that of CD (P<0.05), but no significant differences were found in ADCL between CAP and CD (P>0.05). The ADCPro of BPM was significantly lower than that of CD (P<0.05), but there were no significant differences in ADCL between BPM and CD (P>0.05). The ADCP of CM, CAP, and BPM were significantly higher than that of CD, while that of BSFLM was significantly lower than that of CD (P<0.05), and no significant differences were found in ADCP between TM and CD (P>0.05). To conclude, newly developed protein sources such as single-cell protein (CAP, BPM, and CM) showed great potential as a fishmeal alternative, and insect protein meals (TM and BSFLM) were less effective for shrimp compared to the CD. Although the utilization of CPC by shrimp was lower than other protein sources, it had been much improved compared to the untreated cottonseed meal. The present study will contribute to the application of novel protein sources in shrimp feeds.